PANCASILA AS THE BASIS OF THE LEGAL SYSTEM IN INDONESIA: ANALYSIS OF HOW PANCASILA VALUES FORM THE NATIONAL LEGAL SYSTEM - Siallagan, Dewi Ivana Maria; Sinaga, Rudi Salam (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
Pancasila serves as the foundation of the state and the source of all legal norms in Indonesia. As the nation's ideology and philosophy, the values embedded in Pancasila form the normative basis for the formation, implementation, and enforcement of national law. This paper explores the fundamental role of Pancasila in shaping Indonesia's legal system that upholds justice, humanity, and civility. The writing method used is a literature study with a normative juridical approach. The results show that Pancasila is not merely an ideological symbol but also a substantive guide for legal policymaking aligned with the nation's identity. Therefore, strengthening the implementation of Pancasila values within the legal system is an urgent necessity to realize social justice and uphold the rule of law in Indonesia.